Almas extrañas. El perro entre los waorani de la Amazonía ecuatoriana - Fernando Paniagua Blanc (Nuevo mundo - Mundos Nuevos, 2021)
This article aims to show that, among the Waorani, a hunter-gatherer group of the Amazonian Northwest, dogs take a special position that, although they fulfill the attributes that have generally been associated with the condition of person, in the broad sense with which it is understood in the Amazonian indigenous context, they are excluded from the game of relationships that configure their socio-cosmic world. From this observation the existence of a type of beings is deduced, among which I will show that all those that the Waorani include in the category of cowori are included, whom I have refered to as "strange souls". The existence of this special category allows, in turn, to develop a series of reflections around the mechanisms of understanding regarding those realities that exceed their socio-cosmic space and, therefore, around their process of continued contact with the Western world. Thus, it aspires to contribute to two of the main challenges of Amazonian ontological anthropology: unraveling the ins and outs of the thinking and understanding of hunter-gatherer groups; and try to glimpse how they face their approach to the enveloping Western "modernity".